Model of evaluation delivery of goods in international traffic - Пономарьова, Н. В.; Наумов, В. С.; Бабич, І. А. (Eastern-European Journal of Enterprise Technologies, 2009)
The existing methods of improve of delivery goods in international traffic are analyzed. The mathematical model of the transport process of international freight transport based on Markov chains is given